2021
DOI: 10.1139/cjpp-2020-0547
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of selenium in tacrolimus-induced lung toxicity: potential role of heme oxygenase 1

Abstract: Abstract The present study aimed to evaluate the protective effects of selenium administration against tacrolimus (Tac) induced lung toxicity and to assess the relation between heme oxygenase 1 (HO-1) and these effects. The study was conducted on 36 Wistar male albino rats equally divided into 4 groups: (1) normal control, (2) Selenium (Sel 0.1mg/kg/day p.o for four weeks), (3) TAC 3mg/ml as single oral dose on 27th day (4) Tac + Sel. Lung tissues, lung homogenate, and bronchoalveolar lavage of the sacri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 88 publications
1
3
0
Order By: Relevance
“…Moreover, our IHC results have revealed that there is a parallel glomerular, and tubular expression pattern of Nrf2 and its target downstream proteins with nearly equivalent immunostaining reactivity, which might suggest a functional relationship. Our findings confirm the results reported by Azouz et al [ 41 ], Ibrahim et al [ 42 ], and Gao et al [ 5 ]. Oppositely, the administration of Lina significantly increased the protein expression level of Nrf2 and HO-1 in kidney tissues of TAC-treated rats, as evidenced by an increase of the area % of the immunostaining of the corresponding proteins.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, our IHC results have revealed that there is a parallel glomerular, and tubular expression pattern of Nrf2 and its target downstream proteins with nearly equivalent immunostaining reactivity, which might suggest a functional relationship. Our findings confirm the results reported by Azouz et al [ 41 ], Ibrahim et al [ 42 ], and Gao et al [ 5 ]. Oppositely, the administration of Lina significantly increased the protein expression level of Nrf2 and HO-1 in kidney tissues of TAC-treated rats, as evidenced by an increase of the area % of the immunostaining of the corresponding proteins.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, we have not yet evaluated if restoring pulmonary selenoproteins with postnatal Se supplementation attenuates or prevents altered pulmonary morphometrics. In adult rodents, supplementation with dietary or intraperitoneally delivered Se decreases pulmonary markers of oxidative stress and improves acute lung injury scores after multiple oxidative and inflammatory stressors, including cecal ligation puncture, porcine circovirus type 2 infection, radiation exposure, exhaust inhalation, and tacrolimus, paraquat and aluminum chloride exposure [ 80 , 81 , 82 , 83 , 84 , 85 , 86 ]. Future studies will explore the potential of postnatal Se repletion on impaired alveolar development in our novel animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other inflammatory factors, such as oxidative stress, may also be involved in neutrophil migration. In this study, HO‐1 concentration, a marker of oxidative stress, 21 was also measured in the lung tissue and showed a sustained dose‐dependent increase.…”
Section: Discussionmentioning
confidence: 66%